2017
DOI: 10.1128/genomea.01352-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Bacillus velezensis YJ11-1-4, a Strain with Broad-Spectrum Antimicrobial Activity, Isolated from Traditional Korean Fermented Soybean Paste

Abstract: Bacillus velezensis YJ11-1-4 is a strain that exhibits broad-spectrum antimicrobial activity against various pathogens. It was isolated from doenjang, a traditional Korean fermented soybean paste. The genome comprises a single circular chromosome of 4,006,637 bp with 46.42% G+C content without plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…velezensis is a biocontrol agent that exhibits broad spectrum antimicrobial activity against various foodborne pathogens, and there are no gene families that correlate with human pathogenicity detected in the B . velezensis genome 43 , 44 . Therefore, we presume that the B .…”
Section: Discussionmentioning
confidence: 99%
“…velezensis is a biocontrol agent that exhibits broad spectrum antimicrobial activity against various foodborne pathogens, and there are no gene families that correlate with human pathogenicity detected in the B . velezensis genome 43 , 44 . Therefore, we presume that the B .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study reported that Bacillus velezensis can be used as a biocontrol agent for various plant diseases caused by phytopathogenic fungi [ 30 , 31 ]. Meanwhile, Bacillus velezensis exhibits broad spectrum antimicrobial activity against various foodborne pathogens [ 32 , 33 ], and there are no gene families that correlate with the human pathogenicity detected in the Bacillus velezensis genome [ 34 ]. In summary, Bacillus velezensis is a probiotic that can be used to decontaminate mycotoxins in production practice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these species are frequently detected in fermented foods containing meju and doenjang [24,31,32]. We conclude therefore that B. velezensis may be transferred from environments such as soil to meju, where it becomes a dominant species in during fermentation and then migrates into doenjang [24,31,32].…”
Section: Comparison Of Bacterial Communities Identified Using Culturementioning
confidence: 89%
“…B. velezensis is widely detected in sources such as soil, wheat anthers, and rivers [26][27][28]; and it is used as a biocontrol agent in agriculture [28][29][30]. Furthermore, these species are frequently detected in fermented foods containing meju and doenjang [24,31,32]. We conclude therefore that B. velezensis may be transferred from environments such as soil to meju, where it becomes a dominant species in during fermentation and then migrates into doenjang [24,31,32].…”
Section: Comparison Of Bacterial Communities Identified Using Culturementioning
confidence: 92%